Technique for single axillary incision robotic assisted quadrantectomy and immediate partial breast reconstruction with robotic latissimus dorsi flap harvest for breast cancer: A case report. Issue 27 (July 2018) - Lai, Hung-Wen; Chen, Shou-Tung; Lin, Shih-Lung; Lin, Ya-Ling; Wu, Hwa-Koon; Pai, Shu-Hsin; Chen, Dar-Ren; Kuo, Shou-Jen
Abstract: Rationale: The clinical application of robotic surgery in breast conserving surgery or volume replacement with robotic latissimus dorsi flap harvest (RLDFH) has been rarely reported. In this study, we report the preliminary experience and clinical outcome of robotic assisted quadrantectomy (RAQ) and immediate partial breast reconstruction (IPBR) with RLDFH. Patient concern: Decreasing and avoid back scar length after latissimus dorsi flap harvest. Diagnoses: One 28 years old female with left breast cancer underwent RAQ and IPBR with RLDFH. Initially, she was diagnosed with left breast infiltrating carcinoma that was clinical stage T3N1M0 and triple negative. Interventions: Neoadjuvant chemotherapy consisting of 4 cycles of epirubicin and cyclophosphamide followed by 4 cycles of docetaxel was performed. Breast magnetic resonance imaging showed residual breast cancer about 4.5 cm over the left upper outer quadrant of the breast. Sentinel lymph node biopsy showed no lymph node metastasis. RAQ, which took 82 minutes, was performed first, and the resected breast specimen's weight was 203 gm. She received IPBR with RLDFH, which took 97 minutes. Outcomes: The overall blood loss was 40 mL. The final pathology result was ypT2 (4.2 cm)N0 (sn0/3)M0 and stage IIA. The resection margin was free of tumors. The post-operative recovery was smooth except for seroma formation over the back, which was relieved after repeated aspiration at an outpatient clinic. The patient was satisfied with the post-operative scar and aesthetic outcome. No local recurrence, distant metastasis or case mortality was found during 5 months of follow-up. Lessons: RAQ and IPBR with RLDFH is a safe alternative for small-to-medium-breast-size women with breast cancer who desire breast conservation and are indicated for volume replacement with autologous latissimus dorsi flap.